Изменение свойств пленок кремнийорганических стекол после термической и плазмохимической обработок - Ivanchykau, A. E.; Kisel, A. M.; Medvedeva, A. B; Plebanovich, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
It has been established that the quality of the film after various technological operations in the manufacture of ICs can be assessed by changes in the film's transmission spectrum. This makes it possible to eliminate IC defects caused by metal layer breakage.